Diabetes Research in Children Network:Availability of Protocol Data Sets - Ruedy, Katrina J. (Diabetes Technology Society, 2007)
The Diabetes Research in Children Network (DirecNet) was established in 2001 by the National Institute of Child Health and Human Development and the National Institute of Diabetes and Digestive and Kidney Diseases through special congressional funding for type 1 diabetes research. The network consists of five clinical centers, a coordinating center, and a central laboratory. Since its inception, DirecNet has conducted nine protocols, resulting in 28 published manuscripts with an additional 2 under review and 5 in development. The protocols have involved evaluation of technology available for the treatment of type 1 diabetes, including home glucose meters (OneTouch Ultra, FreeStyle, and BD Logic), continuous glucose monitoring systems (GW2B, CGMS, FreeStyle Navigator, and Guardian RT), and hemoglobin A1c (HbA1c) devices (DCA 2000 and A1cNow). In addition, the group has conducted several studies evaluating factors affecting hypoglycemia, including exercise and bedtime snack composition. The data sets that have resulted from these studies include data from the devices being evaluated, central laboratory glucose, HbA1c and hormone data, clinical center glucose and HbA1c data, accelerometer data, and pump data depending on the procedures involved with each protocol. These data sets are, or will be, available at no charge on the study group's public Web site. Several psychosocial questionnaires developed by DirecNet are also available.